Kesetaraan gender menurut tulisan R.A Kartini dalam perspektif pendidikan Islam - Yani, Anugrah Avi; Jumini, Sri; Nugroho, Muhammad Yusuf Amin (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
This study aims to (1) get a clearer picture and describe related to gender equality in the perspective of R.A Kartini. (2) Knowing how the gender equality perspective of Islamic religious education. (3) Knowing how gender equality according to R.A Kartini's writings in the perspective of Islamic education. This study uses qualitative research methods with the type of library research. With the help of the library, data is obtained from books, journals, articles, etc. The technique of collecting data in this research is by collecting information from scientific books and journals. The data analysis technique used is content analysis technique. Based on the results of this study indicate that gender equality according to R.A Kartini's writings and gender equality in the perspective of Islamic education is the struggle of R.A Kartini to become the goal of Islamic education in liberating women to receive education and R.A Kartini's writings strengthen the principles of Islamic education, both of which are equally elevating the status of women through education.